Customer Satisfaction with Mobile Network Services Provided by Lao Telecommunications Public Company Limited in Luang Namtha Province - Outhensackda, Phaivanh; Yangsansay, Chahue; Onekeo, Sengla (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study investigated customer satisfaction with mobile network services provided by Lao Telecommunications Public Company Limited (Lao Telecom), Luang Namtha Province Branch. The research employed a quantitative approach using a structured questionnaire to collect data from customers. A total of 400 questionnaires were distributed, and 385 valid responses were returned and analyzed according to the research objectives. The findings revealed that overall customer satisfaction with Lao Telecom's mobile network services was at a high level, with a mean score of 4.01. Analysis of individual service dimensions showed that customers reported high levels of satisfaction across all six dimensions evaluated. Among these dimensions, tangibility received the highest satisfaction rating (mean = 4.11), followed by assurance (mean = 4.05), reliability (mean = 3.97), service location (mean = 3.95), empathy (mean = 3.92), and service process (mean = 3.92). The overall mean score across all service dimensions was 4.07, indicating that customers generally perceived the quality of mobile network services positively. The results suggest that Lao Telecom has been successful in delivering services that meet customer expectations across various aspects of service quality. These findings may serve as useful information for management in maintaining service standards and developing strategies to further enhance customer satisfaction and competitiveness in the telecommunications sector.